SELF-CENSORSHIP LICENSED RELIGIOUS OF NEWS MEDIA FOR BALANCED JOURNALISM TO SUPPORT HARMONY AND HUMAN PROGRESS - Amar Ma’ruf (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Religion is a belief in the existence of a supernatural power who created and controls the universe. These days, Islam is often associated with terrorism so as to create Islamophobia. Distortion of information by the media decrease the good image of Islam. These days, many acts of terrorism going on in the world, but if not too highlighted if terrorists are not Muslims. Many civilians have been killed in Palestine, Syria, Afghanistan, and other countries have been killed, but it is not too claimed to be an act of terrorism as well as acts of terrorism that occurred in western countries which incidentally is known culprit is Muslim. One of the ways that have a major impact is the need to be made regarding the rules of self-censorship licensed religious for the news media. Technical implementation of the self-censorship licensed religious use of risk management. The principle is prevention. Prevention of the media to present imbalance in the news much better benefits than giving punishment to the media which wrong in presenting the news. If self-censorship is implemented, not only the equal of news that will be obtained, but the moral improvement of mankind will be achieved, given the media is a tool that easily influence the human mind. Thus proved that the acts of terrorism that confront terrorist act of taking his religion is just a scapegoat in the group seemed to be the face of the religion. Key words: self-cencorship, religious, news, journalism, harmony